2021
DOI: 10.1371/journal.pone.0260619
|View full text |Cite
|
Sign up to set email alerts
|

The impact of conducting preclinical systematic reviews on researchers and their research: A mixed method case study

Abstract: Background Systematic reviews (SRs) are cornerstones of evidence-based medicine and have contributed significantly to breakthroughs since the 1980’s. However, preclinical SRs remain relatively rare despite their many advantages. Since 2011 the Dutch health funding organisation (ZonMw) has run a grant scheme dedicated to promoting the training, coaching and conduct of preclinical SRs. Our study focuses on this funding scheme to investigate the relevance, effects and benefits of conducting preclinical SRs on res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A dermatological study suggested that using multiple public datasets containing human data may enable researchers to test and refine their hypotheses prior to starting animal experiments [ 30 ]. A study on the effects of performing systematic reviews (SRs) on the attitudes and study quality of researchers showed an increased awareness of the limitations of animal studies [ 31 ]. The interviewed researchers noted the poor quality of animal study reports and learned how to improve study quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A dermatological study suggested that using multiple public datasets containing human data may enable researchers to test and refine their hypotheses prior to starting animal experiments [ 30 ]. A study on the effects of performing systematic reviews (SRs) on the attitudes and study quality of researchers showed an increased awareness of the limitations of animal studies [ 31 ]. The interviewed researchers noted the poor quality of animal study reports and learned how to improve study quality.…”
Section: Resultsmentioning
confidence: 99%
“…The interviewed researchers noted the poor quality of animal study reports and learned how to improve study quality. In addition, this study resulted in some researchers deciding to move to clinical trials immediately, instead of performing new animal studies first [ 31 ]. Convincing examples, such as machine learning for read-across toxicity testing and in silico drug trials, have already demonstrated a higher predictive value for humans compared with animal studies [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, to conduct high-quality research, researchers need to be allocated time, understand the importance of research integrity, be trained in best practices, and know about the available tools, such as guidelines for planning and conducting animal-based studies [ 25 , 43 ]. Recently, a case study demonstrated the impact of conducting preclinical systematic reviews on the quality and transparency of research and researchers’ awareness and motivation to promote change within their fields [ 44 ]. A critical comment was that many had not previously known how to report their research adequately, nor had they realized the importance of accurate reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The programme evaluation concluded that the training raised awareness about the value of systematic reviews for research and researchers, as well as the need to bring greater scientific rigour to the conduct of animal studies, leading to an improvement in animal research quality. 48…”
Section: Syrclementioning
confidence: 99%